Combustion Utilization of High-Chlorine Coal: Current Status and Future Prospects - Kang Hong; Tuo Zhou; Man Zhang; Yuyang Zeng; Weicheng Li; Hairui Yang (Energies)
Under China’s “dual carbon” goals (carbon peaking and carbon neutrality), the utilization of high-chlorine coal faces significant challenges due to its abundant reserves in regions such as Xinjiang and its notable environmental impacts. This study systematically investigates the combustion characteristics, environmental risks, and control strategies for high-chlorine coal. Key findings reveal that chlorine release occurs in three distinct stages, namely low-temperature desorption, medium-temperature organic bond cleavage, and high-temperature inorganic decomposition, with release kinetics governed by coal metamorphism and the reaction atmosphere. Chlorine synergistically enhances mercury oxidation through low-activation-energy pathways but exacerbates boiler corrosion via chloride–sulfate interactions. Advanced control technologies—such as water washing, calcium-based sorbents, and integrated pyrolysis–gasification systems—demonstrate substantial emission reductions. However, challenges remain in addressing high-temperature corrosion and optimizing multi-pollutant synergistic control. This study provides critical insights into the clean utilization of high-chlorine coal, supporting sustainable energy transitions.